Antibody-Mediated Autoimmune Diseases of the CNS: Challenges and Approaches to Diagnosis and Management - Sechi, Elia; Flanagan, Eoin P. (Frontiers in Neurology, 2021)
Antibody-mediated disorders of the central nervous system (CNS) are increasingly recognized as neurologic disorders that can be severe and even life-threatening but with the potential for reversibility with appropriate treatment. The expanding spectrum of newly identified autoantibodies targeting glial or neuronal (neural) antigens and associated clinical syndromes (ranging from autoimmune encephalitis to CNS demyelination) has increased diagnostic precision, and allowed critical reinterpretation of nonspecific neurological syndromes historically associated with systemic disorders (e.g., Hashimoto encephalopathy). The intracellular vs cell-surface or synaptic location of the different neural autoantibody targets often helps to predict the clinical characteristics, potential cancer association, and treatment response of the associated syndromes. In particular, autoantibodies targeting intracellular antigens (traditionally termed onconeural autoantibodies) are often associated with cancers, rarely respond well to immunosuppression and have a poor outcome, although exceptions exist. Detection of neural autoantibodies with accurate laboratory assays in patients with compatible clinical-MRI phenotypes allows a definite diagnosis of antibody-mediated CNS disorders, with important therapeutic and prognostic implications. Antibody-mediated CNS disorders are rare, and reliable autoantibody identification is highly dependent on the technique used for detection and pre-test probability. As a consequence, indiscriminate neural autoantibody testing among patients with more common neurologic disorders (e.g., epilepsy, dementia) will necessarily increase the risk of false positivity, so that recognition of high-risk clinical-MRI phenotypes is crucial. A number of emerging clinical settings have recently been recognized to favor development of CNS autoimmunity. These include antibody-mediated CNS disorders following herpes simplex virus encephalitis or occurring in a post-transplant setting, and neurological autoimmunity triggered by TNFα inhibitors or immune checkpoint inhibitors for cancer treatment. Awareness of the range of clinical and radiological manifestations associated with different neural autoantibodies, and the specific settings where autoimmune CNS disorders may occur is crucial to allow rapid diagnosis and early initiation of treatment.